Prenatal and concurrent cocaine, alcohol, marijuana, and tobacco effects on adolescent cognition and attention. (1st October 2018) - Singer, Lynn T.; Min, Meeyoung O.; Minnes, Sonia; Short, Elizabeth; Lewis, Barbara; Lang, Adelaide; Wu, Miaoping
Highlights: Prenatal cocaine/polydrug exposure (PCE) may lead to substance (SUDs) through associated cognitive deficits and early substance use. PCE and non-exposed adolescents were compared on cognitive functions and drug use. PCE adolescents had deficits in Perceptual Reasoning IQ and visual attention. Adolescent substance use predicted attentional deficits in addition to PCE. PCE affects neurocognitive functions associated with SUDs. Abstract: Background: Prenatal cocaine/polydrug exposure (PCE) may increase vulnerability to substance use disorders due to associated cognitive deficits. We examined whether neurocognitive deficits in executive functions and attention observed in PCE children persisted to adolescence when compared to non-cocaine/polydrug (NCE) children, and whether adolescent substance use (tobacco, alcohol, marijuana) was also associated with neurocognitive deficits. Methods: 354 (180 PCE, 174 NCE) adolescents in a longitudinal study from birth were administered the Wechsler Intelligence Scales for Children - IV (WISC-IV), and the Integrated Visual and Auditory Continuous Performance Test (IVA/CPT) at age 15.5. Assessments of prenatal exposure to cocaine, alcohol, marijuana, and tobacco and measures of use at age 15.5 were taken. Confounding factors measured included lead, the caregiving environment, and violence exposure. Relationships between drug use and prenatal exposures on outcomes were assessed through multiple regression. Results: Adolescents with PCE had deficits in Perceptual Reasoning IQ and visual attention. Prenatal alcohol exposure predicted verbal and working memory IQ and visual and auditory attention deficits. Adolescent tobacco, alcohol, and marijuana use predicted attention in addition to PCE, lead and the caregiving environment. Conclusion: Prenatal cocaine and alcohol exposure and adolescent use of substances are associated with neurocognitive deficits known to increase vulnerability to SUDs.